The Structural Model of Democratic Parenting Based on Parental Stress Index and Couples' Communication Patterns with the Mediating Role of Wisdom - Moeini, Freshteh; Hosseinpour, Reza; Jafari, Alireza (Applied Family Therapy Journal (AFTJ), 2025)
Objective: The present study aimed to examine the structural model of the relationship between parental stress and couples' communication patterns with democratic parenting, with the mediating role of wisdom.Methods: The research method was applied in nature, considering the potential use of the data, and the design was descriptive-correlational. The statistical population consisted of parents of elementary school students in Tehran during the 2022-2023 academic year, from which 639 participants were selected through cluster sampling. Data collection tools included the Parental Stress Index by Abidin (1990), the Couples' Communication Patterns Scale by Christensen and Salovey (1984), the Sense of Coherence Scale by Antonovsky (1993), and the Authoritative Parenting Questionnaire by Robinson et al. (2001). The data were analyzed using structural equation modeling (SEM).Findings: The results showed that the stress index, demand/withdrawal, and criticism/defense patterns had a significant negative relationship with authoritative parenting (P < 0.01). Wisdom and constructive interactions demonstrated a positive relationship with authoritative parenting (P < 0.01). Additionally, the results of the modeling indicated that the model had a good fit, and wisdom could mediate the relationship between parental stress, constructive interactions, and demand/withdrawal with authoritative parenting.Conclusion: The findings showed that the variables of parental stress, couples' communication patterns, and wisdom influence parenting.